Evaluating the Impact of Dentists on Preventive Oral Healthcare and Community Well-Being: A Systematic Review - Alqahtani, Ali Othman Awad; M Asiri, Mohammed Alhussain; Asiri, Awd Hizam Ali; Asiri, Mofareh Hassan; Asiri, Mofareh Mohammed; Derham, Ahmad Saeed (Journal of Posthumanism, 2024)
Preventive oral healthcare is a critical component of public health, and dentists play a central role in reducing the global burden of dental diseases and enhancing community well-being. This systematic review examines evidence from 2016 to 2025 to evaluate the impact of dentist-led preventive interventions across clinical, educational, community, and system-level domains. Findings demonstrate that preventive dental services—including fluoride varnish, sealants, and early diagnostic screenings—significantly decrease caries incidence, periodontal disease progression, and tooth loss. Dentist-delivered education and behavioral counseling were found to improve oral hygiene practices, dietary choices, and oral health literacy, contributing to sustainable long-term health behaviors. Community-based programs and outreach initiatives led by dentists increased access to preventive care, particularly among underserved populations, while interdisciplinary collaborations and innovations such as teledentistry enhanced early detection of oral and systemic conditions. Collectively, the evidence shows that dentists contribute not only to improved oral health outcomes but also to broader community well-being through enhanced quality of life, reduced healthcare costs, and strengthened public health systems. Despite progress, disparities in access and long-term outcome data remain areas requiring further attention. Strengthening preventive dentistry is essential for promoting equitable and sustainable community health